2022
DOI: 10.1002/pat.5645
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐matrix gas separation membranes for sustainable future: A mini review

Abstract: Mixed‐matrix membranes (MMMs), merging the advantages of polymers and inorganic fillers, has become a preferable choice as future gas separation membrane. Owing to hierarchical structures, MMMs are suitable for high‐performance gas separation capability. Research on extended porous organic/inorganic materials also known as fillers of intrinsic nanopores (FINS) such as porous organic frameworks (POFs), Zeolites, metal–organic frameworks (MOFs), porous organic cages (POCs) and analogous metal–organic polyhedral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 120 publications
(213 reference statements)
0
6
0
Order By: Relevance
“…The development of defect-free MMM is considered challenging as its fabrication suffers from polymer filler incompatibility. Poor interaction between polymer and filler that leads to the formation of non-selective voids can cause pore blockage, polymer rigidification and sieve-in-cage morphology, which deteriorates membrane performance [ 161 ]. Thus, having good polymer-filler compatibility is important.…”
Section: Mixed Matrix Membranesmentioning
confidence: 99%
“…The development of defect-free MMM is considered challenging as its fabrication suffers from polymer filler incompatibility. Poor interaction between polymer and filler that leads to the formation of non-selective voids can cause pore blockage, polymer rigidification and sieve-in-cage morphology, which deteriorates membrane performance [ 161 ]. Thus, having good polymer-filler compatibility is important.…”
Section: Mixed Matrix Membranesmentioning
confidence: 99%
“…Both experimental and computational studies showed that many MOF and COF membranes can exhibit high gas permeabilities. , Synthesis of thin-film membranes from crystalline materials is challenging due to many issues such as poor interactions with the substrates, crack formation, and moisture instability, which affect the practical implementation and scalability of thin-film MOF and COF membranes . Therefore, MOFs and COFs have been recently used as filler particles in polymers to make MMMs . Incorporation of MOFs as fillers into polymers has led to many MOF/polymer MMMs, which offer higher gas permeability and/or selectivity than the pure polymer membrane, but these MMMs generally suffer from compatibility issues between MOFs and polymers due to the inorganic nature of MOFs .…”
Section: Introductionmentioning
confidence: 99%
“…19 Therefore, MOFs and COFs have been recently used as filler particles in polymers to make MMMs. 20 Incorporation of MOFs as fillers into polymers has led to many MOF/polymer MMMs, which offer higher gas permeability and/or selectivity than the pure polymer membrane, but these MMMs generally suffer from compatibility issues between MOFs and polymers due to the inorganic nature of MOFs. 21 On the other hand, COFs offer better interfacial compatibility with polymers compared to MOFs thanks to the completely organic structure of COFs.…”
Section: Introductionmentioning
confidence: 99%
“…These membranes combine the exceptional separation capabilities of molecular sieve materials with the cost-effectiveness of organic polymer materials. [1][2][3][4][5][6] The inorganic materials employed as the dispersed phase in the construction of MMMs possess distinctive chemical structures and exceptional mechanical strength. Their incorporation into the polymer matrix not only enhances the membrane's mechanical and thermal durability but also augments its separation capabilities.…”
Section: Introductionmentioning
confidence: 99%